Corruption in the Iberian empires (Albuquerque)
viii, 228 sayfa
Keywords: “This book provides new perspectives into a subject that historians have largely overlooked. The contributors use fresh archival research from Spain, Portugal, Brazil, Bolivia, Mexico, and the Philippines to examine the lives of slaves and farmworkers as well as self-serving magistrates, bishops, and traders in contraband. The authors show that corruption was a powerful discourse in the Atlantic world. Investigative judges could dismiss culprits, jail them, or, sometimes, have them 'garroted and their corpses publicly displayed.'“ --